Summer undergraduate biomedical research program for underrepresented minority students in a rural, low-income state - Anders, Michael E.; Prince, Latrina Y.; Williams, Tremaine B.; McGehee, Robert E.; Thomas, Billy R.; Allen, Antino R. (Frontiers in Public Health, 2024)
Diversity can enhance the agenda and quality of biomedical research, but a dearth of underrepresented minorities and women serve as biomedical researchers. The study purpose was to examine the impact of a summer undergraduate research program on self-efficacy in research, scientific communication, and leadership as well as scientific identity, valuing objectives of the scientific community, and intent to pursue a biomedical research career. Underrepresented minority and female undergraduate students participated in a mentored research experience in a rural, low-income state. Students’ self-efficacy in research, scientific communication, and leadership as well as scientific identity, valuing objectives of the scientific community, and intent to pursue a biomedical research career increased post-program compared to pre-program.